Typical value of the mean glandular dose in Full-field Digital mammography at the Public Hospital in Brazil - Frederico L. Alvarenga; Camila Engler; Peterson L. Squair; Maria do Socorro Nogueira (Brazilian Journal of Radiation Sciences)
The mean glandular dose (MGD) provides dosimetric information about the quantity of radiation received by the mammary glands during mammographic exposures. There is, therefore, the need to analyse the radiation dose received by patients presenting for mammography examinations. This study presents the establishment of typical values for the mean glandular dose (MGD) in full-field digital mammography (FFDM) in a public hospital in Brasil. The research responds to the International Commission on Radiological Protection (ICRP) guidelines and aims to optimize radiation doses while ensuring the diagnostic quality of mammograms. By analyzing DICOM images obtained from patients, typical MGD values were calculated for different compressed breast thicknesses (CBT). The study involves a comprehensive review of exposure parameters and patient data, extracted via the Volpara Manager Dose software and DICOM Header. The results provide an essential reference for local Diagnostic Reference Levels (DRLs) in mammography, supporting ongoing efforts to enhance imaging safety and image quality. These findings also provide a framework for the future implementation of local DRLs across public hospitals, emphasizing the importance of consistent radiation dose management in mammography.